2014
DOI: 10.1109/tuffc.2014.006316
|View full text |Cite
|
Sign up to set email alerts
|

Removal of residual nuclei following a cavitation event using low-amplitude ultrasound

Abstract: Microscopic residual bubble nuclei can persist on the order of 1 second following a cavitation event. These bubbles can limit the efficacy of ultrasound therapies such as shock wave lithotripsy and histotripsy, as they attenuate pulses that arrive subsequent to their formation and seed repetitive cavitation activity at a discrete set of sites (cavitation memory). Here, we explore a strategy for the removal of these residual bubbles following a cavitation event, using low amplitude ultrasound pulses to stimulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
44
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(46 citation statements)
references
References 47 publications
2
44
0
Order By: Relevance
“…This secondary Bjerknes force is hypothesized to be the dominant mechanism bringing the remnant bubbles from SWL cavitation together to coalesce and clear the propagation path. 1,20 In general, the degree of coalescence required for effective clearance of the propagation path to mitigate effects of bubble shielding is not known. This suggests the potential for further optimization of acoustic parameters for ABC for further improvement in fragmentation efficiency.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This secondary Bjerknes force is hypothesized to be the dominant mechanism bringing the remnant bubbles from SWL cavitation together to coalesce and clear the propagation path. 1,20 In general, the degree of coalescence required for effective clearance of the propagation path to mitigate effects of bubble shielding is not known. This suggests the potential for further optimization of acoustic parameters for ABC for further improvement in fragmentation efficiency.…”
Section: Discussionmentioning
confidence: 99%
“…2 In our previous studies, low-amplitude acoustic bursts were used with in vitro models to actively remove residual cavitation bubbles through forced coalescence. 1,19,20 Significant improvement was demonstrated in the comminution efficacy of SWL at higher rates (120 and 60 SW/minute). In this study, the feasibility of SWL stone comminution at 120 SW/minute with acoustic bubble coalescence (ABC) was evaluated on a porcine model and compared to standard SWL at the same rate.…”
Section: Introductionmentioning
confidence: 96%
“…The experimental setup used to investigate the effects of bubble removal pulse frequency was the same as that described previously [23], with the addition of a needle hydrophone (Müller-Platte Needle Probe 100-100-1, Dr. Müller Instruments, Oberursel, Germany) positioned adjacent to the histotripsy transducer focus at an offset distance of 2 mm, distal relative to the bubble removal module (Fig. 1).…”
Section: Methodsmentioning
confidence: 99%
“…In our previous work we have explored a strategy for the active removal of these remnant nuclei following a cavitation event [23], with the ultimate goal of mitigating the ill-effects of residual bubbles in cavitation-based ultrasound therapies. It was shown that the application of appropriately designed low amplitude ultrasound pulses can stimulate the aggregation and subsequent coalescence of residual bubble nuclei, in effect removing them from the field.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation